Comparison of biochemical and cytotoxic activities of extracts obtained from dorsal spines and caudal fin of adult and juvenile non-native Caribbean lionfish (Pterois volitans/miles). (October 2017) - Sáenz, Aránzazu; Ortiz, Natalia; Lomonte, Bruno; Rucavado, Alexandra; Díaz, Cecilia
Abstract: Pterois volitans/miles lionfish (adult and juvenile) dorsal spines and caudal fin extracts were compared in their general composition, enzymatic activities and hemolytic and cytotoxic effects on bovine aortic endothelial cells and murine myoblasts, to distinguish between the activities present in the venom and epidermal mucus. Intradermal and intramuscular injections were also administered in mice to determine in vivo effects. This work shows that crude venom of Caribbean species of lionfish, present in dorsal spines, induces several in vitro effects including hemolysis, weak cytotoxicity, proteolytic and hyaluronidase activities, whereas in vivo, it is not hemorrhagic nor myotoxic, but causes edema, plasma extravasation and a thrombotic-associated lesion on the skin. Some small differences were observed between adult and juvenile venomous secretions. Gelatinolytic activity of the epidermal mucus, the only activity found in caudal fin extracts, could contribute to the in vivo toxicity of the venom. Highlights: Lionfish crude venom induces significant hemolysis and weak cytotoxicity in endothelial cells and myoblasts. In vivo lionfish crude venom induces a lesion in the skin probably as the result of a thrombotic effect. Lionfish venom is not hemorrhagic nor myotoxic, but induces edema and vascular congestion. Gelatinolytic activity is decreased by EDTA, indicating the presence of metalloproteinases, both in crude venom and mucus.